The strawberry patch pancake house - Gilmore, Laurie (Gilmore, Laurie. Dream Harbor series, 2025)
"Fall in love with the brand new spring romance set in Dream Harbor, from the bestselling author of The Pumpkin Spice Cafe and The Cinnamon Bun Book Store. As a world-renowned chef, single dad Archer never planned on moving to a small town, let alone running a pancake restaurant. But Dream Harbor needs a new chef, and Archer needs a community to help raise his daughter, Olive. Iris has never managed to hold down a job for more than a few months. So when it's suggested that Archer is looking for a live-in nanny, she almost runs in the opposite direction. Now, Iris finds herself in a whole new world. One where her gorgeous new boss lives right across the hall and likes to cook topless... Keeping everything strictly professional should be easy, right?"--